2016
DOI: 10.1007/s11655-015-2437-2
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated effects of Jianpi Qushi herbs on patients receiving FOLFOX4 after colorectal cancer surgery: A meta-analysis

Abstract: JPQS herbs can improve the quality of life for patients undergoing FOLFOX4 treatment after colorectal cancer surgery, relieve symptoms, and somewhat reduce the adverse effects of FOLFOX4 regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The obstruction of the blood and blood vessels will lead to the loss of the healthy qi , and insufficient healthy qi will result in the imbalance of yin and yang . Moreover, long-term dietary disorders, weakness of the spleen and stomach, dysfunction of the internal organs, and the internal growth of evil toxins and eventually lead to blood stasis [ 15 , 16 ]. Chemotherapy is detrimental to the healthy qi and causes deficiency of the spleen.…”
Section: Discussionmentioning
confidence: 99%
“…The obstruction of the blood and blood vessels will lead to the loss of the healthy qi , and insufficient healthy qi will result in the imbalance of yin and yang . Moreover, long-term dietary disorders, weakness of the spleen and stomach, dysfunction of the internal organs, and the internal growth of evil toxins and eventually lead to blood stasis [ 15 , 16 ]. Chemotherapy is detrimental to the healthy qi and causes deficiency of the spleen.…”
Section: Discussionmentioning
confidence: 99%
“…Our further subgroup analysis reveal that TCM has a tendency to further reduce the risk of metastatic recurrence in elderly (no less than 60 years old) female patients, and has the same tendency in patients with rectal cancer, adenocarcinoma, poorly differentiation, stage III disease, comorbidities, or chemotherapy. We consider that may be related to the role of TCM in efficacy enhancing and toxicity reducing, improving immunity and quality of life [ 17 – 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that patients with stage I CRC on either side did not benefit from TCM, whereas subjects with stage II-III LSCRC or RSCC who were administered TCM exhibited a distinct advantage in decreasing the risk of recurrence and metastasis; however, this advantage was not statistically significant in subjects with stage II RSCC. We thought that the primary reasons why TCM improved DFS of CRC on both sides lie in the advantages of TCM in attenuating toxicity, improving immunity and quality of life and enhancing medication sensitivity in patients with tumors, which can prevent metastasis and extend survival[ 13 - 17 ].…”
Section: Discussionmentioning
confidence: 99%